Nanocompósito de poli(oxido de etileno) reforçado com nanocristais de celulose extraídos da fibra de tucum - Vasques, José Carlos (2018)
The using of a nonrenewable resources in the production of new materials, in particular synthetics plastics, it is a cause for concern and environmental call ones due to its long degradability time. Although a lot of thermoplastics are passing by recycling this it is not a common activity in the world which makes the biodegradable materials researches a viable alternative to minimize environment impacts. Advances in researches on natural fibers and the development of composites and nanocomposites it is one of the challenges for obtaining new materials produced by renewable sources. There are great advantages when using natural fibers rather than synthetic fibers as plastic reinforcement like: abundance due to the enormous variety of plants available in biodiversity, comes from renewable resource, high biodegradability and low density. The natural lignocellulosic fibers of Tucum studied are among the least known and investigated. Few researches show results about its structural characteristics and reinforced polymer nanocomposites with them. The head of this research was prepare and characterize nanocomposites constituted by polyoxyethylene (POE) reinforced with cellulose nanocrystals extracted from Tucum fibers by solvent evaporation. To determine the chemical, thermal and morphological characterization of the fibers, nanocrystals and reinforced polymer was used tensile testing, x-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), dynamic mechanical analysis (DMTA), scanning electron microscopy (SEM) and field emission scanning electron microscopy (FESEM).